Typification of two Stereocaulon names (Lecanorales, Ascomycota) - Oset, Magdalena; Kukwa, Martin (Phytotaxa, 2014)
The nomenclature, bibliographic citations and typifications of the names Stereocaulon botryosum and S. condensatum are discussed. A neotype is designated for S. condensatum and the lectotypification of S. botryosum is clarified. In addition, the morphological and chemical characteristics of both species and information on exsiccates examined are presented.